EFEKTIVITAS APLIKASI SIMKAH SEBAGAI UPAYA PENCEGAHAN MANIPULASI DATA DALAM ADMINISTRASI PENCATATAN NIKAH DI KUA KECAMATAN SOKAN KABUPATEN MELAWI - Kobat, Damia Mahfuzah; Ardiansyah, Ardiansyah; Fadhil, Moh (Al-Usroh, 2024)
This Study of this research were to find out: 1) How is the effectiveness of SIMKAH at the KUA Kec. Sokan Kab. Melawi 2) The SIMKAH application be can used as an effort to prevent data manipulation in the administration of marriage registration. This study used descriptive qualitative research, namely the method is based on phenomena occur in the field. The approach taken was a qualitative approach where the researcher conducted interviews and documentation. In this study, the data sources used were primary and secondary data. The results of this study conclude that: 1) The SIMKAH at KUA Kec. Sokan Kab. Melawi is quite effective, although there is still much to be considered, especially the problem of internet networks and infrastructure to support the SIMKAH service process. 2) The SIMKAH can prevent data manipulation in the administration of marriage registration at the KUA Kec. Sokan Kab. Melawi by cooperating with the nearest KUA and dukcapil.